2014
DOI: 10.4028/www.scientific.net/kem.600.657
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Performance of Asphalt Mixtures with Natural Aggregates and Recycled Aggregates for Surface Course

Abstract: The recycled aggregates of construction and demolition solid waste can be used on pavements to decrease environmental impacts in cities. Thus, this study aimed to compare the mechanical performance of asphaltic mixtures made with natural aggregates and concrete recycled aggregates for surface course of pavements. The materials were collected in an asphalt mixing plant and in a construction and demolition solid waste recycling plant located in João Pessoa/PB, Brazil. The Marshall asphalt mix design was chosen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Nevertheless, for the Marshall flow number, it was observed that 5.0% (of total weight of aggregates) was slightly lower than the minimum threshold values (2.5-3.5 mm) stipulated by the Spanish technical specifications (Spanish Ministry of Public Works, 2015) and others researchers (Behnood et al, 2015;Djakfar et al, 2015;Hou et al, 2017;Marques et al, 2014;Pasandín and Pérez, 2013;Pérez et al, 2013;Rafi et al, 2011) and that the more the bitumen content added into the preliminary mix design, the better the mixture behavior (when it is loaded during the Marshall stability test), except for 6.0% binder content. Therefore, it can be concluded that 5.5% binder content (of the total weight of aggregates) was discarded for this research study since it delivers/offers much lower mechanical performance properties in terms of rutting with the wheel tracker (EN 12697-22:2008+A1).…”
Section: Fatigue Resistancementioning
confidence: 76%
“…Nevertheless, for the Marshall flow number, it was observed that 5.0% (of total weight of aggregates) was slightly lower than the minimum threshold values (2.5-3.5 mm) stipulated by the Spanish technical specifications (Spanish Ministry of Public Works, 2015) and others researchers (Behnood et al, 2015;Djakfar et al, 2015;Hou et al, 2017;Marques et al, 2014;Pasandín and Pérez, 2013;Pérez et al, 2013;Rafi et al, 2011) and that the more the bitumen content added into the preliminary mix design, the better the mixture behavior (when it is loaded during the Marshall stability test), except for 6.0% binder content. Therefore, it can be concluded that 5.5% binder content (of the total weight of aggregates) was discarded for this research study since it delivers/offers much lower mechanical performance properties in terms of rutting with the wheel tracker (EN 12697-22:2008+A1).…”
Section: Fatigue Resistancementioning
confidence: 76%